What are the problems and suggestions related to cancer health education in Sichuan, China? A qualitative study of community health workers (CHWs) - Zhonghua Yang; Qingqing Wang; Fang Yi; Linglin Zhang; Yuting Li; Lilou Rong; Shaoping Wan (BMC Health Services Research)
Abstract Background Health education conducted by community health workers (CHWs) is an evidence-based strategy for promoting cancer prevention, cancer screening, and adherence to medical guidance from doctors. However, CHWs are confronted with some problems related to cancer health education in China. This study aimed to clarify CHWs’ awareness of problems in cancer health education in China and the solutions that they were considering to improve the quality and efficiency of cancer health education. Methods A qualitative descriptive design with purposive sampling was applied in eight primary health care sectors in Guangyuan and Chengdu in Sichuan, China. Face-to-face, in-depth, semistructured interviews were conducted, and a total of 60 CHWs were interviewed. The interviews were transcribed verbatim and imported into Nvivo12.0. Thematic analysis using the constant comparative method was used to analyze the data. Results Uncooperative inhabitants, poor organization, low-frequency provision, and inadequate training for CHWs were problems related to cancer health education provided by CHWs in China. CHWs proposed some suggestions to improve the accessibility and acceptability of cancer health education, including combining online and offline education, health education after screening, cancer plus others, health education in the workplace, and volunteer recruitment. Conclusions Both the problems and suggestions described in this study may provide evidence for cancer health education and policy-making related to cancer prevention and control in China.